MANAJEMEN INTEGRASI GADGET SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DI SEKOLAH DASAR - Anah Nurhasanah; Asep Jaya; Okke Rosmala Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the management of gadget integration as an interactive learning medium to improve the quality of learning in elementary schools. Using the Systematic Literature Review (SLR) method with PRISMA procedures , this study synthesized 30 scientific articles from Google Scholar, SINTA, and Scopus databases for the 2021–2025 period. The results indicate that gadget integration effectively enhances students' motivation, active engagement, and learning outcomes. However, this effectiveness highly depends on systematic management, including planning learning objectives, organizing usage rules, implementing gadgets as interactive media, and supervising to minimize distractions. This management framework is essential to ensure that gadget use in elementary schools is well-directed, effective, and sustainable.